Ruthenium catalyzed direct asymmetric reductive amination of simple aliphatic ketones using ammonium iodide and hydrogen - Ghosh, Tamal; Ernst, Martin; Hashmi, A. Stephen K.; Schaub, Thomas (European journal of organic chemistry, 2020)
On the direct asymmetric reductive amination of aliphatic ketones to primary amines: By using Ru‐Binaphane as catalyst and NH4I as the amine source, it is possible to aminate prochiral aliphatic ketones with moderate ee values up to 74 %.
Gesehen am 02.09.2020